1987
DOI: 10.1002/ana.410220408
|View full text |Cite
|
Sign up to set email alerts
|

Positron emission tomography study of human brain functional development

Abstract: From over 100 children studied with 2-deoxy-2[18F]fluoro-D-glucose and positron emission tomography we selected 29 children (aged 5 days to 15.1 years) who had suffered transient neurological events not significantly affecting normal neurodevelopment. These 29 children were reasonably representative of normal children and provided an otherwise unobtainable population in which to study developmental changes in local cerebral metabolic rates for glucose (lCMRGlc). In infants less than 5 weeks old lCMRGlc was hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

45
588
7
13

Year Published

1990
1990
2008
2008

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 1,388 publications
(653 citation statements)
references
References 50 publications
45
588
7
13
Order By: Relevance
“…Previous studies in monkeys (Kennedy et al, 1982), humans (Chugani and Phelps, 1986;Chugani et al, 1987), and rats (Nehlig et al, 1988) have found a relationship between a developmental in crease of lCMRglc in a particular brain structure and the emergence of behavior mediated by that struc ture. In the present studies, we also find a general relationship between metabolic and behavioral de velopment in the kitten, as discussed below.…”
Section: Correlation Between Lcmr G Lc and Neurobehavioral Developmentmentioning
confidence: 89%
See 2 more Smart Citations
“…Previous studies in monkeys (Kennedy et al, 1982), humans (Chugani and Phelps, 1986;Chugani et al, 1987), and rats (Nehlig et al, 1988) have found a relationship between a developmental in crease of lCMRglc in a particular brain structure and the emergence of behavior mediated by that struc ture. In the present studies, we also find a general relationship between metabolic and behavioral de velopment in the kitten, as discussed below.…”
Section: Correlation Between Lcmr G Lc and Neurobehavioral Developmentmentioning
confidence: 89%
“…This developmental period (15 to 60 days) corresponds to the time of rapid synaptic proliferation known to occur in the cat. At 90 and 120 days, a slight decline in lCMRglc Using positron emission tomography (PET), we have previously described the distribution and ab solute rates of local cerebral glucose utilization in the normal human brain from birth to adulthood (Chugani and Phelps, 1986;Chugani et al, 1987 Abbreviations used: BHB, f3-hydroxybutyrate ; 2DG, 2-deoxyglucose; PET, positron emission tomography . …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…H. Johnson, 2001;Paus, 2005), whereas MTL regions mature at relatively faster rates (Casey, Giedd, & Thomas, 2000;Gogtay et al, 2004;Ofen et al, 2007;Sowell et al, 2003; but see Gogtay et al, 2006). The differential developmental trajectories of brain regions suggest that the zone of maximum functional development progresses from MTL to neocortical PFC areas (Chugani, Phelps, & Mazziotta, 1987; for computational modeling, see Shrager & Johnson, 1996). With respect to brain aging, PFC regions are among the first to show signs of senescence-related deterioration during adulthood (Hedden & Gabrieli, 2004;Park & Gutchess, 2005;Raz et al, 2005).…”
Section: Life-span Differences In Neural Correlates Of Strategic and mentioning
confidence: 99%
“…Similarly, the prefrontal cortex is not fully myelinated until mid-to-late adolescence (Giedd et al, 1999;Klingberg et al, 1999;Sowell et al, 1999;Yakovlev, 1962;Yakovlev & Lecours, 1967). Synaptogenesis occurs at the same rate in most cortical regions (Rakic, Bourgeois, Eckenhoff, Zecevic, & Goldman-Rakic, 1986), although the prefrontal cortex may lag behind the rest of the brain (Chugani, Phelps, & Mazziotta, 1987;Huttenlocher, 1979). White matter may also undergo protracted development within anterior brain regions (Klingberg et al, 1999;Sowell et al, 1999).…”
mentioning
confidence: 99%